To solve this problem it is necessary to apply the kinematic equations of motion for speed and distance, as well as the concepts related to kinetic energy.
The change in the height of a body subject to gravity is given by
[tex]h = \frac{1}{2} gt^2 \rightarrow t = \sqrt{\frac{2h}{g}}[/tex]
Where
h = Height
g =Gravity
t = time
Replacing with our values we have that the time is
[tex]t = \sqrt{\frac{2h}{g}}[/tex]
[tex]t = \sqrt{\frac{2(192)}{9.8}}[/tex]
[tex]t = 6.25s[/tex]
From speed as a function of change between acceleration and time we have then that after 2.6 seconds the speed would be
[tex]g = \frac{v}{t} \rightarrow v = g*t[/tex]
[tex]v = 9.8*2.6[/tex]
[tex]v = 25.48m/s[/tex]
The kinetic energy would be given by
[tex]KE = \frac{1}{2} mv^2[/tex]
[tex]KE = \frac{1}{2} (84)(25.48)[/tex]
[tex]KE = 1070.16J[/tex]
Therefore the kinetic energy after 2.6s is 1070.16J